Nilai-nilai Pendidikan Karakter Integritas dalam Novel Buya Hamka - Aini, Rasidah; Fatria, Fita (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Character education is an important part of the educational process which aims to form individuals with good personalities and high morality. The importance of character education increases in the modern era, where moral and ethical challenges are increasingly complex. Literature, as a form of art and human expression, is very good at conveying the principles of character education. This study can also contribute to understanding how literature can be an effective means of conveying moral messages to readers. This research uses a descriptive qualitative research approach. This approach focuses on the meaning, experience, and context surrounding the phenomenon under study. The data source in this research is the novel "Buya Hamka" by A. Fuadi, first printed in 2013 with 364 pages by PT Falcon. This research data is in the form of dialogue and story exposure that contains the values ??of integrity character education. The main instrument in this research is the researcher himself. The results of this research are the values ??of integrity character education contained in the novel "Buya Hamka" by A. Fuadi, namely honesty, responsibility, independence, simplicity, hard work, courage, fairness and caring.